(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The unique coronavirus disease (COVID-19) surprised the world, and as of early April 2020, the virus has claimed over 80,000 lives and infected over a million people worldwide. Most governments used social distancing, area-wide lockdowns and curfews, and contact tracing of those under investigation to battle the pandemic. Some heads of state employed ’friendlier’ techniques, including infographics, infomercials, and hashtags, to encourage people to take preventative actions. Furthermore, other governments have used fairly harsh measures to manage conduct, preying on people’s concerns. Despite valiant efforts by governments to support businesses and protect jobs through job retention programs, millions of tourism workers still have lost their jobs, and self-employed individuals have seen their earnings drop. Small and medium-sized businesses require special assistance implementing workplace health and safety procedures. Make employment services more flexible, modern, and safe as well.